The Proverbial Fool: The Book of Proverbs and ‘Biblical’ Counseling - Wyse, R. R. (Verbum et ecclesia, 1996)
How can the book of Proverbs be utilized in the context of Christian counseling? This topic is the focal point of my dissertation, in which 1 seek to integrate the areas of Biblical Srudies and Pastoral Theology in order to provide an informed and responsible answer to this question. In the following article select aspects of that study are highlighted, touching upon such concerns as (1) How biblical are so-called "biblical" counselors? - with J Adams and L Crabb examined as representative writers; (2) What hermeneutical considerations should such Christian counselors have in mind when interpreting Proverbs? - where current advances in the study of proverbs are used to sharpen the understanding and use of Proverbs; (3) How could the above considerations, coupled with an exegetical study on "the foolish" in Proverbs (10-29), be utilized to make Adams’ and Crabb's "biblical" proposals more representative and reflective of Scripture?; and lastly, (4) How could an understanding of the "world of Proverbs’’ be incorporated into the "language-world" of the counseling context?